Exploring factors constraining utilization of contraceptive services among adolescents in Southeast Nigeria: an application of the socio-ecological model - Uchenna Ezenwaka; Chinyere Mbachu; Nkoli Ezumah; Irene Eze; Chibuike Agu; Ifunanya Agu; Obinna Onwujekwe (BMC, 2020)
Abstract Background High rate of teenage pregnancy in Nigeria is potentially an indication of poor access to and utilization of contraceptives among this age group. This paper presents findings from in-depth exploration of perceived barriers to utilization of contraceptive services by adolescents. Methods A qualitative study was conducted in six communities in Ebonyi state, southeast Nigeria. Eighty-one in-depth interviews and six focus group discussions were conducted. Respondents comprised policy makers, community leaders, health service providers and parents of adolescents. Pre-tested interview guides were used to collect information on perceived barriers to utilization of contraceptive services by adolescents. All interviews were audio recorded and transcribed in English. Data was analysed using thematic framework approach, and the socio-ecological model was adapted for data synthesis. Results Individual level factors that limit access to contraceptives for adolescents include lack of awareness and poor knowledge, fear of side effects, low self-esteem, and inability to afford cost of services. Interpersonal (family-related) barriers to access include poor parent-child communication of sexual and reproductive health matters and negative attitude of parents towards to sexuality education for adolescents. Health systems barriers to accessing contraceptives for adolescents include lack of privacy and confidentiality, stock-out of contraceptive commodities, judgmental attitude of health workers, insufficient staff that are skilled in adolescent sexual and reproductive health. Gendered cultural norms, societal shaming and religious intolerance also preclude adolescents from accessing and using contraceptive services. Wider societal factors such as negative peer and media influence, absence of sexuality education in schools, lack of social networks in communities; and macro level factors such as poor economic conditions were also perceived to limit access to contraceptives for adolescents. Conclusion Utilization of contraception is constrained by an interplay of factors acting at various levels. Addressing these barriers could contribute to improved access to contraceptive services for adolescents, as well as reduction in unwanted teenage pregnancy.